Simulation and Evaluation of Sponge City Reconstruction Effect in Urban Drainage Residential Area - YU Haijun; FAN Yuyan; CAO Daling; CHEN Wei (Renmin Zhujiang)
Drainage effect evaluation is a necessary links in the construction of Sponge City,and urban rainfall mathematical models are important supporting tools for the evaluation work.Taking a residential area in Beijing City as an example,a refined drainage model of the study area was constructed based on a coupled 1D and 2D hydrodynamic model for urban rainstorms,and the drainage situation before and after the sponge transformation of the drainage system were simulated and analyzed.The results showed that the constructed model can well reflect the real drainage situation of the community,and the proposed drainage system upgrade plan can effectively improve the drainage capacity in the area,and the overflow and submergence were significantly reduced.The research can provide some technical reference for the simulation of the hydraulic condition of drainage community and the construction and management of Sponge City.